2007
DOI: 10.3748/wjg.v13.i2.276
|View full text |Cite
|
Sign up to set email alerts
|

Role of ciprofloxacin in patients with cholestasis after endoscopic retrograde cholangiopancreatography

Abstract: AIM: To d e t e r m i n e t h e r o l e o f c i p r o f l o x a c i n i n reducing cholangitis in cholestatic patients with adequate biliary drainage after endoscopic retrograde cholangiopancreatography (ERCP). METHODS:A ra n d o m i z e d , c o n t r o l l e d t r i a l w a s performed in 48 cholestatic patients at Rajavithi Hospital (Tertiary Referral Center for ERCP: 600 cases per year). All the 48 patients received 200 mg ciprofloxacin intravenous injection for 30 min before starting any procedures, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Prophylactic use of antibiotics as part of ERCP cannot reliably affect BB or cholangitis. Again, even biliary excreted Ciprofloxacin does not provide uniform protection against post-ERCP cholangitis[2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic use of antibiotics as part of ERCP cannot reliably affect BB or cholangitis. Again, even biliary excreted Ciprofloxacin does not provide uniform protection against post-ERCP cholangitis[2].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an analysis of Medicare patients (1992-2007) showed that one in two patients already has a PBD at the time of the surgical consultation[1]. The disadvantage is that ERCP leads almost always to bacterobilia (BB)[2-4]. BB is a risk factor (up to factor 2) for surgical site infection[5-9].…”
Section: Introductionmentioning
confidence: 99%